OBSTRUCTIVE SLEEP APNEA IN ESRD PATIENTS ON MAINTENANCE HEMODIALYSIS: A CROSS SECTIONAL OBSERVATIONAL STUDY - Nadia Bashir; Abid Ahmad Kuchay; Shamsudeen M P; Raja Karthik Kalindidi; Gangadhar Taduri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Approximately 10–36% of the general population have moderate-severe OSA..OSA is far more common in CKD populations, with prevalence rates of over 40% .Furthermore, it has been shown that the prevalence of OSA is further increased in more advanced stages of CKD .Although this does not necessarily imply a causal relationship given that both conditions are associated with similar comorbidities such as hypertension, diabetes, and obesity, there is definite biological plausibility to support a role for OSA in the pathogenesis of accelerated decline in kidney function. The prevalence is higher in patients with chronic kidney disease (CKD) due to the presence of classical risk factors like obesity but also to factors peculiar to uremia and dialysis Material and Methods: This study was conducted in the department of Nephrology in a tertiary care institute in South India. Patients of End stage renal disease on maintainance hemodialysis were interviewed for OSA questionaires including Stop Bang Questionnaire, Berlin Questionnaire and Epsworth Sleepiness Score. 152 cases were studied in the study. Results: Of the three questionnaires, the risk of OSA as per Stop Bang Questionnaire was 27% (41/152); as per Berlin questionnaire and Epworth sleepiness score were 21.7% (33/152) and 21.1% (32/152), respectively. Conclusion: Obstructive sleep apnea is more common among ESRD patients on hemodialysis. Stage 5 chronic kidney disease patients should be screened for OSA risk with questionairres, preferably Stop Bang Questionaire.